b - b d 9; 9; University of Dhaka. Alumni Association (b, 2010)
Contributed articles by former students of the University of Dhaka, Bangladesh, about their university and the alumni; souvenir volume released during a conference held in the university in 2009, on the occasion of completion of sixty years of its Alumni Association; conference organized by the association.
In Bengali; includes articles in English.
Keywords: University of Dhaka -- Congresses; University of Dhaka -- Alumni and alumnae -- Congresses; Universities and colleges -- Bangladesh -- Dhaka -- Congresses; Universities and colleges -- Alumni and alumnae -- Bangladesh -- Dhaka -- Congresses; Education